Immunomodulatory effects and mechanisms of the extracts and secondary compounds of Zingiber and Alpinia species: a review - Yuandani; Jantan, Ibrahim; Haque, Md. Areeful; Rohani, Ade Sri; Nugraha, Sony Eka; Salim, Emil; Septama, Abdi Wira; Juwita, Nur Aira; Khairunnisa, Nur Aini; Nasution, Halimah Raina; Utami, Dinda Sari; Ibrahim, Sarah (Frontiers in Pharmacology, 2023)
Zingiber and Alpinia species (family: Zingiberaceae) are popularly used in food as spices and flavouringflavoring agents and in ethnomedicine to heal numerous diseases including immune-related disorders. However, their ethnomedicinal uses have not been sufficiently supported by scientific investigations. Numerous studies on the modulating effects of the plantsplants and their bioactive compounds on the different steps of immune system have been documented. This review aimed to highlight up-to-date research findings and critically analyzedelaborate In this review, the modulatory effects and mechanisms of the extracts and secondary compounds of several Zingiber and Alpinia species, viz.